Assessing the Validity of Open-Source Biographical Data in Terrorism Research - Eylem Kanol; Maria-Anna Hirth (Terrorism and Political Violence, 2024)
A multitude of studies in terrorism research depend on biographical data gathered through the cliometric method. This technique entails reconstructing and aggregating demographic and socio-economic data on terrorism offenders from publicly accessible sources. A notable limitation of this method is the substantial number of missing values. Researchers often employ this data collection strategy as comprehensive official sources are not publicly accessible and are rarely provided to researchers due to privacy concerns, among other factors. In this study, we analyze original data on 53 convicted Islamist terrorism offenders, collected from both publicly available media data and court records. We concentrate on and compare a number of demographic, socio-economic, and biographic variables. The insights derived from these analyses hold important implications for the reliability of biographical research that relies on open-source data.
Keywords: 320; Open-source data; data validity; terrorism data; biographical research; court files